Generalizations of Troisi’s inequality in weighted p-Sobolev spaces with singularities - Hua Chen; Yong Luo; Jing Wang (Journal of Inequalities and Applications, 2019)
Abstract We extend classical Troisi’s inequality to the weighted p-Sobolev spaces on stretched cone, edge, and corner respectively. The results here can be used to investigate anisotropic elliptic equations involving cone degeneracy, edge degeneracy, and corner degeneracy, which will be studied in our forthcoming papers.